2017
DOI: 10.1002/jnr.24115
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of thalamo‐cortical connectivity after brain injury: recovery of consciousness, complex behavior, or passage of time?

Abstract: In 2000, a landmark case report described the concurrent restoration of consciousness and thalamo-frontal connectivity after severe brain injury (Laureys et al., 2000). Being a single case however, this study could not disambiguate whether the result was specific to the restoration of consciousness per se as opposed to the return of complex cognitive function in general or simply the temporal evolution of post-injury pathophysiological events. To test whether the restoration of thalamo-cortical connectivity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 84 publications
2
32
1
Order By: Relevance
“…Monti et al demonstrated with fMRI that a small proportion of patients with DOC had brain activation while performing some mental-imagery tasks, suggesting some awareness and cognition [15]. Another study demonstrated an association between restoration of thalamo-frontal connectivity based on resting state fMRI data and the recovery of cognitive function [17]. Furthermore, functional connectivity analysis in another resting state fMRI study [18] showed that the default mode network, frontoparietal, salience, auditory, sensorimotor, and visual networks had a high discriminative capacity (>80%) for separating patients with MCS and UWS.…”
Section: Introductionmentioning
confidence: 99%
“…Monti et al demonstrated with fMRI that a small proportion of patients with DOC had brain activation while performing some mental-imagery tasks, suggesting some awareness and cognition [15]. Another study demonstrated an association between restoration of thalamo-frontal connectivity based on resting state fMRI data and the recovery of cognitive function [17]. Furthermore, functional connectivity analysis in another resting state fMRI study [18] showed that the default mode network, frontoparietal, salience, auditory, sensorimotor, and visual networks had a high discriminative capacity (>80%) for separating patients with MCS and UWS.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] Imaging biomarkers are appealing because they are based on noninvasive procedures that are routinely performed as part of a patient's workup protocol and are capable of detecting patterns across the whole brain that may indicate or precede epileptogenesis. [23][24][25][26] Imaging biomarkers are appealing because they are based on noninvasive procedures that are routinely performed as part of a patient's workup protocol and are capable of detecting patterns across the whole brain that may indicate or precede epileptogenesis.…”
Section: How Imaging May Inform Pathomechanisms Of Ptementioning
confidence: 99%
“…Several studies have attempted to identify the progression of injury with longitudinal imaging acquisition, 25,26,53,[91][92][93] but the need for imaging at multiple time points in association with PTE remains unmet. To adequately assess the utility of imaging biomarkers and secure a mechanistic understanding of PTE, the progression of various imaging phenotypes across sequential imaging sessions must be understood.…”
Section: Biomarker Acquisition and Quantificationmentioning
confidence: 99%
See 2 more Smart Citations